When do middlemen matter? Evidence from variation in corruption in India. Issue 3 (20th September 2017) - Bussell, Jennifer
Abstract : Corruption is a persistent problem in developing countries, and recent scholarship suggests that middlemen play an important role in corrupt acts. Yet, while intermediaries can reduce transaction costs in illicit exchange, they also increase agency costs and reduce benefits to others. The involvement of middlemen may thus vary. I argue that middlemen are most likely to engage in, and benefit from, the subset of corruption transactions that are repeated frequently, but not by the same parties. I test the implications of this argument using survey experiments administered to a large sample of politicians and bureaucrats at multiple levels of government in India. I show that middlemen are critical, but far from ubiquitous. Intermediaries are more relevant where corrupt deals are frequent but involve unfamiliar potential principals. My results suggest that anticorruption efforts must pay greater attention to the type of corruption and the incentives of middlemen.